Des objets au croisement des disciplines : Les facettes éco-paysagères de Guinée Maritime - Elisabeth Leciak (VertigO, 2008)
The meeting between social analysis and ecological diagnosis is an important issue for environmental sciences. Nevertheless interactions between nature and culture exist at various levels of integration and, to describe ecosystems/societies co-evolution, researches are first required to identify valid functional scales corresponding to ecological processes and social phenomena as well. In Coastal Guinea, our study concerned spatial entities where local uses and practices of land are integrated with ecological functions in a concrete entity, a hybrid of nature and culture. Allowing the simultaneous deployment of the methods of social sciences and ecological sciences, these patches of landscape are described like ecosystems but also like objects of local representations and social stakes.